2021
DOI: 10.1152/jn.00585.2020
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in proprioception predict the extent of implicit sensorimotor adaptation

Abstract: Recent studies have revealed an upper bound in motor adaptation, beyond which other learning systems may be recruited. The factors determining this upper bound are poorly understood. The multisensory integration hypothesis states that this limit arises from opposing responses to visual and proprioceptive feedback. As individuals adapt to a visual perturbation, they experience an increasing proprioceptive error in the opposite direction, and the upper bound is the point where these two error signals reach an eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 74 publications
(96 reference statements)
4
57
1
Order By: Relevance
“…As such, this method eliminates the potentially confounding effects of strategic processes (McDougle et al, 2016; Kim et al, 2020). Nonetheless, participants’ reach angles gradually shift in the direction opposite to the clamp and shows the cardinal signatures of implicit motor adaptation without awareness (Morehead et al, 2017; Kim et al, 2018, 2019; Parvin et al, 2018; Tsay et al, 2020a, 2020b, 2021a, 2021b; Avraham et al, 2021; Poh et al, 2021; Vandevoorde and Orban de Xivry, 2019; Yin and Wei, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…As such, this method eliminates the potentially confounding effects of strategic processes (McDougle et al, 2016; Kim et al, 2020). Nonetheless, participants’ reach angles gradually shift in the direction opposite to the clamp and shows the cardinal signatures of implicit motor adaptation without awareness (Morehead et al, 2017; Kim et al, 2018, 2019; Parvin et al, 2018; Tsay et al, 2020a, 2020b, 2021a, 2021b; Avraham et al, 2021; Poh et al, 2021; Vandevoorde and Orban de Xivry, 2019; Yin and Wei, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…The transient sensory events associated with a target jump or flash might siphon attention away from the visual feedback, thereby weakening the overall learning signal. Alternatively, a transient distraction may have increased the likelihood that visual feedback is mis-localized, thus attenuating the motor system’s reliance on this uncertain feedback (Burge et al, 2008; Konrad P. Körding & Wolpert, 2004; Tsay, Avraham, et al, 2020; Tsay, Kim, Parvin, Stover, & Ivry, 2021; Wei & Körding, 2010). Regardless of the mechanism, our results underscore the importance of considering the distractive effect of a target jump manipulation and the consequences of this on implicit recalibration.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach, we were able to increase our sample size in an efficient manner, providing greater power to detect subtle differences between target jump conditions. We used an motor learning platform (OnPoint) (Tsay, Lee, et al, 2020, 2021) and recruited participants using Amazon Mechanical Turk. Despite substantial differences between in-person and online sensorimotor learning experiments (e.g., in-person: dark room to occlude vision of the hand; online: full visibility of the hand for trackpad users), we have found that the results obtained online are quite similar to those obtained in-person (Tsay, Lee, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Second, within-participant designs may result in possible transfer/order effects, which can be difficult to nullify even with counterbalancing. For instance, adaptation that incorporates explicit strategies is faster in a second session (also known as savings) [47,35,85,86,42], and implicit adaptation has been shown to attenuate upon re-learning [47,87,88,89].…”
Section: Moving Forward With the Onpoint Platformmentioning
confidence: 99%